P855 The impact of the severe financial crisis on drug persistence and disease course in IBD patients in Lebanon. (30th January 2023) - Sharara, A; Ibrahim, M A; Allam, J; Haidar-Ahmad, D; Chalhoub, C; Francis, R
Abstract: Background: Lebanon is currently going through an unprecedented financial crisis (considered as one of the worst in the world in modern times) that has affected all aspects of everyday life. In particular, the economical crash has significantly crippled the Lebanese healthcare sector, resulting in severe shortages of basic drugs and medications, most of which cannot be produced locally. Patients with chronic diseases including those with Inflammatory Bowel Disease (IBD) have been impacted most given their need for costly and chronic treatment including biologics. Methods: We collected data using a 12-question web survey disseminated through social media platforms of the patient organization, I Battle Disease . The questions aimed to explore the patients' ability to acquire the necessary medications, whether they had to alter or completely stop their treatment, and any resulting complications (forced corticosteroid use, hospitalization, or surgery) it had on the course of their disease. Results: 102 patients completed the survey. The patients were nearly evenly split between Crohn's disease (53%) and ulcerative colitis (47%). Adalimumab was the most commonly used medication before the economic crisis (30%), followed by infliximab (18%), vedolizumab (10%), ustekinumab (8%), and tofacitinib (8%). Azathioprine and 5-ASA monotherapy were used by 8% and 19% of patients respectively. All biologics and small molecules used to be covered fully by third party payors including the National Social Security Fund (38%), the Ministry of Public Health (22%), and private insurance (18%). As a result of the crisis, the majority of patients (69%) declared stopping or interrupting their treatment in the past 3 years, with most (46%) having interrupted treatment for >12 months. 22% of patients reported switching to azathioprine due to issue in access to biologics. Additionally, 69% of patients reported worsening of their condition after stopping treatment, resulting in forced steroid use (36%), switching to another medication (36%), or unscheduled hospital admission (15%). Further, 66% of participants confirmed that they had to purchase their medications from abroad or through a local private vendor using out-of-pocket foreign currencies. Finally, 12% of patients reported that they had to immigrate or seek employment abroad due to difficulty with drug access. Conclusion: The recent financial and economic events in Lebanon have imposed significant challenges on patients with IBD, affecting their adherence to therapy and consequently the control of their disease. There is an urgent need for action within the public health context to improve IBD medication availability and accessibility for the Lebanese population.